Control de stock en el Comercial Distribuidora Touma S.A en la ciudad de Babahoyo en el año 2023. - Cegido Cabezas, Diego David (2024)
In this context, a detailed investigation was carried out on stock control at Distribuidora Touma S.A. The main objective of this research was to evaluate the efficiency of stock control at Distribuidora Touma S.A., identifying specific challenges and proposing solutions to improve inventory management. We sought to gain a detailed understanding of staff perception and experience, as well as the owner's strategic approach to addressing existing challenges. Adopting a descriptive methodological approach, techniques such as interviews with management personnel, surveys of suppliers and clients, and the application of structured questionnaires were used. The data collection instruments included interview and survey questionnaires, with the purpose of obtaining qualitative and quantitative information on inventory management at Distribuidora Touma S.A. The results of the survey addressed to employees revealed that 67% perceive the efficiency of stock control as inefficient, where solutions were proposed, with the review and adjustment of replenishment processes being the most notable, according to 67% of participants. The investigation reveals a worrying discrepancy between the importance attributed to inventory control and the operational reality at Distribuidora Touma S.A. Identified challenges, such as lack of accuracy and fluctuations in product availability, point to the urgent need for improvements. Recommendations include implementing a more advanced inventory management system, reviewing logistics processes and training staff.